Evidence-based practice: Guidance for using everolimus in combination with low-exposure calcineurin inhibitors as initial immunosuppression in kidney transplant patients - Pascual, Julio; Berger, Stefan P.; Chadban, Steven J.; Citterio, Franco; Kamar, Nassim; Hesselink, Dennis A.; Legendre, Christophe; Eisenberger, Ute; Oppenheimer, Federico; Russ, Graeme R.; Sommerer, Claudia; Rigotti, Paolo; et al. (Transplantation reviews, 2019)
The mammalian target of rapamycin (mTOR) inhibitor, everolimus, in combination with reduced-exposure calcineurin inhibitor (CNI), has been demonstrated in clinical trials to have comparable efficacy in low-to-moderate immunological risk kidney transplant recipients to the Standard of Care, mycophenolic acid (MPA) in combination with standard-exposure CNI. Current treatment guidelines consider mTOR inhibitors to be a second-line therapy in the majority of cases; however, given that everolimus-based regimens are associated with a reduced rate of viral infections after transplantation, their wider use could have great benefits for kidney transplant patients. In this evidence-based practice guideline, we consider the de novo use of everolimus in kidney transplant recipients. The main outcomes of our consideration of the available evidence are that: 1. Everolimus, in combination with reduced-exposure CNI and low dose steroids, is a suitable regimen for the prophylaxis of kidney transplant rejection in the majority of low-to-moderate immunological risk adult patients, with individualized management; 2. Induction with either basiliximab or rabbit anti-thymocyte globulin is an effective therapy for kidney transplant recipients when initiating an everolimus-based, reduced-exposure CNI regimen; and 3. An individualized approach should be adopted when managing kidney transplant recipients on everolimus-based therapy.